Esthetic Rehabilitation with Lithium Disilicate Veneers (International Journal of Medical and Surgical Sciences, 2016)
Because the aesthetic results and preservation of tooth structure, lithium disilicate veneers are indicated for the aesthetic treatment of anterior teeth with abnormal shape, size and color. The aim of this report was to demonstrate the steps in oral rehabilitation using lithium disilicate veneers. The patient had teeth diastemas from 15 to 25; gene- ral and oral clinical examination was performed, and study models were obtained. waxed diagnosis was made based on the DSD and Mockup was drawn with addition silicone; the laboratory fabricate veneers lithium disilicate were cemented by adhesive technique. Veneers allowed a conservative, functional and aesthetic rehabilitation treatment of our patient.